Analisis Implementasi Kebijakan Ketransmigrasian di Dinas Tenagakerja Transmigrasi dan Kependudukan Provinsi Jawa Timur Periode 2009-2014 - Achluddin Ibnu Rochim (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2017)
Apolicy of democratization and decentralization of development post-Orde Baru in Indonesia. Policies that result in deregulation in all sectors of the Indonesian government is bringing new value changes in the bureaucracy and the public. The potential for conflict of interest, the social and the clash of value systems in recipient community development agents and different backgrounds gave dynamics consequence such as a conflict between migrants with the local population. In practice there is ambivalence policy sector development transmigration, on one side of Pancasila as the ideal basic, the Undang-Undang 1945 contains the values of National unity and togetherness becomes the basis for public policy itself, but on the other hand precisely into contention for the benefit of the Local Government following each value, traditions and culture of different peoples. A discrepancy between the situation of communities and local government conditions sender with the community and the local government transmigration, formulated: 1.How is the Implementation of Transmigration Sector Development Policy in East Java Province, 2.How to model the Implementation of Transmigration Sector Development Policy in East Java Province. Design methods of research used a qualitative descriptive data mining technique documents, interviews, and observations to the location of transmigration.Â